THE TEACHERS’ AND STUDENTS’ PERCEPTIONS TOWARDS A MODEL OF FEEDBACK AND STUDENTS’ MOTIVATION ON SECOND GRADE STUDENTS OF SMK NEGERI 3 SINGARAJA IN ACADEMIC YEAR 2015/2016THE TEACHERS’ AND STUDENTS’ PERCEPTIONS TOWARDS A MODEL OF FEEDBACK AND STUDENTS’ MOTIVATION ON SECOND GRADE STUDENTS OF SMK NEGERI 3 SINGARAJA IN ACADEMIC YEAR 2015/2016 - ., Nadia Santa; ., Made Hery Santoso, S.Pd, M.Pd.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menganalisis persepsi guru dan siswa terhadap sebuah model dari umpan balik yang diberikan oleh guru pada hasil kerja siswa dan dalam proses pengerjaan tugas. Selain itu, tingkat motivasi siswa yang dipengaruhi oleh pemberian umpan balik pada hasil kerja siswa dan dalam proses pengerjaan tugas dalam pandangan guru dan siswa juga dianalis. Penelitian ini dilakukan berdasarkan pada masalah yang didapat pada saat melakukan observasi di SMK Negeri 3 Singaraja. Permasalahannya adalah terkadang guru kurang memperhatikan kebutuhan, karakter dan tingkat pemahaman siswa dalam memberikan umpan balik, serta keefektifan umpan balik belum diketahui. Metode yang digunakan untuk mengumpulkan data adalah kuesioner dan panduan wawancara. Data dianalisis secara deskriptif kuantitatif. Hasil dari penelitian ini adalah mayoritas guru dan siswa memiliki persepsi positif terhadap umpan balik yang diberikan oleh guru pada hasil kerja siswa dan dalam proses pengerjaan tugas. Disamping itu, hasil tingkat motivasi siswa dalam belajar bahasa Inggris yang dipengaruhi oleh umpan balik yang diberikan oleh guru pada hasil kerja siswa dan dalam proses pengerjaan tugas dalam pandangan guru dan siswa adalah mayoritas siswa memiliki tingkat motivasi yang tinggi. Dapat disimpulkan bahwa, baik guru maupun siswa memiliki persepsi positif terhadap umpan balik yang diberikan dan mayoritas siswa memiliki tingkat motivasi yang di tinggi yang dipengaruhi oleh umpan balik yang diberikan. Kata Kunci : persepsi guru, persepsi siswa, tingkat motivasi siswa, model umpan balik. This research was aimed at analyzing teachers’ and students’ perceptions towards a model of feedback given by teachers in task and process level. Besides, students’ level of motivation affected by feedback given in students’ task and during task accomplishment viewed by teachers and students were also analyzed. This research was conducted based on the problem gained while researcher doing observation in SMK Negeri 3 Singaraja. The problems are sometimes teachers did not notice students’ needs, character and level of understanding in giving feedback, also the effectiveness of feedback not yet known. Method used in obtained the data are questionnaire and interview guide. The data analyzed by using descriptive quantitative design. The result of this study is most of teachers and students have positive perceptions on feedback given by teachers in students’ task and process accomplishing task. Besides that, the result of students’ level of motivation affected by feedback given by teachers in students’ task and process accomplishing task in the view of teachers and students is most of students have high level of motivation. It can be concluded that both teachers and students have positive perceptions on feedback given and most of students have high level of motivation affected by feedback given.keyword : teachers’ perceptions, students’ perceptions, students’ level of motivation, a model of feedback.